Strengthening Women’s Inclusion in Social Accountability Initiatives - Nazneen, Sohela; Silva Olivares, Maria Fernanda (2021)
In the last 20 years, social accountability initiatives have facilitated the inclusion and participation of marginalised groups in governance processes. This Policy Briefing focuses on how and what factors prove effective in strengthening women’s voice in processes holding public service providers accountable. We argue that initiatives must: (a) build technical and other forms of capacity amongst women; (b) change formal rules on women’s inclusion; (c) apply political economy analysis to unpack power dynamics, identify actors in favour of gender equality, and build a network in support of women; and (d) make long-term funding commitments for sustainable change in gender-biased norms.
Keywords: *tagged; L - english / inglês; accountability / responsabilização; gender / género; social inclusion & exclusion / inclusão e exclusão social